Understanding statistical concepts in laboratory quality control measures in biomedical research - Juneja, Atul; Anand, Apoorva (International Journal of Research in Medical Sciences, 2017)
The purpose of this article is to explore the quality assurance methods in carrying out laboratory investigations on various kits and biological products and analysing the results through statistical approach. This is commonly used in the health care industry where biological investigations have become a very important part. Quality Control/Quality Assurance (QC/QA) refers to the overall management system which includes the organization, planning, data collection, quality control, documentation, evaluation and reporting activities. With the emerging health issues and availability of modern treatment modalities, it is important to provide the patient, clinical diagnosis with the relevant laboratory investigations. It is therefore, important to maintain the quality control of the testing with a standard degree of precision, which in turn is essential for the delivery of the quality patient care. In view of this, statistical approaches that can be adopted to ascertain the quality of the test have been discussed. The communication also discusses components of validity of the biomedical test and its relevance in clinical settings.